2020
DOI: 10.3390/v13010053
|View full text |Cite
|
Sign up to set email alerts
|

Protein Disulfide Isomerase A4 Is Involved in Genome Uncoating during Human Astrovirus Cell Entry

Abstract: Although human astroviruses (HAstVs) are important agents of gastroenteritis in young children, the studies aimed at characterizing their biology have been limited, in particular regarding their cell entry process. It has been shown that HAstV serotype 8 enters human cells by a classical clathrin-mediated endocytosis pathway; however, the cell receptor or other cell entry factors that may be relevant for an efficient viral infection are unknown. In this work we used a far-Western blotting approach to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The same study reported that siRNAs targeting PDIA1, PDIA3, and PDIA4 also inhibited the replication of influenza A and B viruses in vitro . 16F16 was also recently reported to inhibit human astrovirus types 1 and 8 ( 167 ). Also, LOC14, a reversible small molecule inhibitor of PDIA1 and PDIA3, had an efficient effect in decreasing viral burden and inflammation in primary tracheal epithelial cells infected with FLUAV.…”
Section: Inhibitors Of Er Chaperones As Antiviral Therapeutic Agentsmentioning
confidence: 90%
See 1 more Smart Citation
“…The same study reported that siRNAs targeting PDIA1, PDIA3, and PDIA4 also inhibited the replication of influenza A and B viruses in vitro . 16F16 was also recently reported to inhibit human astrovirus types 1 and 8 ( 167 ). Also, LOC14, a reversible small molecule inhibitor of PDIA1 and PDIA3, had an efficient effect in decreasing viral burden and inflammation in primary tracheal epithelial cells infected with FLUAV.…”
Section: Inhibitors Of Er Chaperones As Antiviral Therapeutic Agentsmentioning
confidence: 90%
“…2 ). PDIs have also been shown to be essential for rotavirus cell entry ( 165 ) and to be required for astrovirus type 8 uncoating during cell entry (PDIA4) ( 167 ).…”
Section: Other Er Chaperonesmentioning
confidence: 99%
“…3-Methyltoxoflavin is a potent PDI inhibitor, with an IC 50 of 170 nM 25 and we hypothesize that the mechanism for the activity of 3-methyltoxoflavin may be due in part to inhibition of PDI 25 . PDI is a promising target for cancer therapy 25, 27 and many viruses, such as HIV 28 , CHIKV 29 , Dengue 30, 31 , Zika 31 , Hepatitis C 32 , influenza 33 , as well as others 34 . 3-Methyltoxoflavin also induces Nrf2 antioxidant response, ER stress response, and autophagy 25 .…”
Section: Resultsmentioning
confidence: 99%
“…PDIs were shown to be involved in viral entry of dengue virus by interaction with nonstructural protein 1 ( 145 ) and regulating integrin activity ( 146 ). PDIs bind capsid spike proteins of human astroviruses, the cause of gastroenteritis, thereby inhibiting viral entry, more precisely uncoating of the viral genome ( 147 ). PDIs regulate the redox state of hemagglutinin and neuraminidase and thereby virus attachment and influenza infection ( 148 , 149 ).…”
Section: Thiol Switches In Bacterial and Viral Infectionsmentioning
confidence: 99%